Efficiency Evaluation of Medical Security Payment DRG - Xiaowei Chang (Forest Chemicals Review)
Based on the brief introduction of the development status, grouping strategy and evaluation efficiency index of DRG medical insurance payment system, this paper analyzes the efficiency of a certain place’s medical data from 2017 to 2019. From the analysis results, it can be seen that the use of the DRG system for medical insurance payment can improve the hospital’s medical service ability and efficiency, and the hospital’s medical safety quality management has been improved. It is hoped that it will be helpful to promote nationwide payment according to DRGs.